Euphorbia sahyadrica (Euphorbiaceae), a new species of succulent shrub from the wet zone of the northern Western Ghats, Maharashtra, India - Malpure, Nilesh V.; Raut, Prashant S.; Sardesai, Milind M.; de Jong, Bruce E. (Phytotaxa, 2021)
Euphorbia sahyadrica (Euphorbiaceae), a new succulent species belonging to Euphorbia subg. Euphorbia sect. Euphorbia is described and illustrated from the Raigad district of Maharashtra, India. It is related to E. nivulia but differs in its shrub-like habit, bark with closely-packed horizontal branch scars, elliptical-shaped leaf with short petiole and easily visible lateral veins, protruding tubercles with two pairs of spines per spine shield, bisexual cyathia in the central sessile position on the cyme, and capsules that have laterally tapering cocci without bulging suture lines between the cocci.